2016
DOI: 10.1177/2321023016634909
|View full text |Cite
|
Sign up to set email alerts
|

India’s States: The Struggle to Govern

Abstract: This article analyzes recent variations in governing strategies in different Indian states. Those variations mean that the 'Indian state', as citizens experience it, takes different forms in different states. Between 1989 and mid-2014, no single party could gain a parliamentary majority. That caused a major decentralization of power away from the once dominant Prime Minister's Office-horizontally to other institutions at the national level, and vertically downward to governments at the state level. Ironically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It has also been suggested that the Indian court has been strengthened by a political context in which no party was able to form a government on its own between 1989 and 2014. This severely eroded the central government's ability to centralise power and to interfere with the functioning of the country's institutions (Manor 2016). The Court has been able to fill 'a governance vacuum' (Deva 2009: 30) created by a series of weak central governments.…”
Section: The Courts and The Governmentmentioning
confidence: 99%
“…It has also been suggested that the Indian court has been strengthened by a political context in which no party was able to form a government on its own between 1989 and 2014. This severely eroded the central government's ability to centralise power and to interfere with the functioning of the country's institutions (Manor 2016). The Court has been able to fill 'a governance vacuum' (Deva 2009: 30) created by a series of weak central governments.…”
Section: The Courts and The Governmentmentioning
confidence: 99%
“…Not all of this has happened licitly: States' new regulatory powers under the economic-liberalization regime have allowed chief ministers to collect rents and set up shady funding streams for use in managing the political process. 21 State-level elections were once known as tough for incumbents to win, but this pattern gave way in the 2000s to the phenomenon of the chief minister with a secure grip on office (Modi in Gujarat being a case in point). The shrewdest chief ministers even learned how to leverage the states' role as primary implementers of many policies to steal credit for popular programs whose plans and resources in fact came from New Delhi.…”
Section: Is the Center Too Weak?mentioning
confidence: 99%